Investigating women with postmenopausal bleeding: The utility of endometrial thickness in transvaginal ultrasound. (29th May 2020) - Palipana, Dinesh; Fomin, Igor; Russell, Elsa; Chan, Brian; Wong, Chad; Chan, Erick; Ho, Debbie; Walker, Graeme
Abstract : Background: Australian clinical guidelines recommend further investigation in females with postmenopausal bleeding (PMB) and endometrial thickness (ET) of ≥4 mm on transvaginal ultrasound (TVUS). However, the literature indicates that an ET of ≥3 mm as an upper limit is a more sensitive predictor of endometrial malignancy (EM) in females with PMB. Aims: To assess whether Australian guidelines for PMB with an upper limit of 4 mm ET on ultrasound investigation, is sensitive enough for malignancy detection. Material and Methods: A retrospective study was performed on tissue results in PMB presentations to the Gold Coast Hospital and Health Service between 2011 and 2015. Results: Twenty point nine percent of women with PMB had a malignancy. With an upper limit of 4 mm in ET on ultrasound, malignancy was present in 22% of participants. [Correction added on 10 July 2020, after first online publication: percentage of women with PMB that had a malignancy has been amended to twenty point nine percent.] Conclusions: A limit of 3 mm for ET in PMB, along with office endometrial biopsy, should be considered to ensure timely diagnoses.